MEMBANGUN SITUASI KERJA YANG LEBIH MENYENANGKAN PADA KARYAWAN DENGAN PENGADAAN MINUMAN YANG BERGIZI TINGGI - Arundati Shinta; Bimono .; Esti Listiari (Universitas Negeri Makassar, 2015)
Objective of this research is to verify the relationship between the availability of the free of charge of nutritious drink with the pleasing work situation. The second objective is to verify the relationship between the free of charge of nutritious drink with the pro-environment behavior emergence. Thirty (17 women, 13 men) employees participate in this research. They have consumed free of charge of nutrition drink. This research revealed that the free of charge of the nutrition drink enhance more the work situation, compare to the non-free of charge (chi-square = 7.778, asymptotic significance .005 or p <.01). The second result is that the free of charge of the nutritious drink supports more the pro-environment behavior emergence, compare to the non-free of charge (chi-square = 4.537, asymptotic significance .033 or p<.01). The pro-environment behavior is also sustained by their willingness to bring some household packaging waste.